2008
DOI: 10.4049/jimmunol.181.10.7205
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype Switching by Inflammation-Inducing Polarized Th17 Cells, but Not by Th1 Cells

Abstract: Analyses of inflammation inducing Th cells revealed that a portion of these cells express both IFN‐γ and IL‐17, suggesting that Th1 and/or Th17 may switch their phenotype. Here, we examined phenotype retention in a system in which polarized Th1 or Th17 cells specific against hen egg lysozyme (HEL) induce ocular inflammation in recipient mice expressing HEL in their eyes. Whereas no switching to Th17 was detected in Th1 recipient eyes, substantial proportions of transferred Th17 expressed IFN‐γ, or both IFN‐γ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
137
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(154 citation statements)
references
References 33 publications
14
137
2
1
Order By: Relevance
“…Interestingly, the decrease in Th17-DP cell number in cultures containing exogenous IL-2 coincided with a corresponding increase in Foxp3 1 T cells while an increase in Th17-DP cells in a IL-2 low environment (culture without exogenous IL-2) was associated with corresponding diminution in the number of Foxp3 1 T cells (Fig. 4B), suggesting that IL-2 might promote plasticity of T-cell subsets, particularly Th17 cells [22][23][24][25][26].…”
Section: Th17-dp Cells Have a Selective Growth Advantage In A Low Il-mentioning
confidence: 90%
“…Interestingly, the decrease in Th17-DP cell number in cultures containing exogenous IL-2 coincided with a corresponding increase in Foxp3 1 T cells while an increase in Th17-DP cells in a IL-2 low environment (culture without exogenous IL-2) was associated with corresponding diminution in the number of Foxp3 1 T cells (Fig. 4B), suggesting that IL-2 might promote plasticity of T-cell subsets, particularly Th17 cells [22][23][24][25][26].…”
Section: Th17-dp Cells Have a Selective Growth Advantage In A Low Il-mentioning
confidence: 90%
“…Murine Th1 and Th17 cultures were cultured, as previously reported (32). Human peripheral CD4 + CCR6 − and CD4 + CCR6 + cells were cultured in IL-2 alone (Th0) or with Th17 polarizing cytokines (Th17).…”
Section: Methodsmentioning
confidence: 99%
“…IFN-c). This Th17 phenotype instability was discovered initially using TCR transgenic CD4 + T cells polarized in vitro towards Th17 cells, [83][84][85][86] and more recently with highly purified IL-17A + or IL-17F + populations isolated by cytokine-capture assays 85,87,88 or by cell sorting based on surface expression of reporters (such as Thy-1.1, red fluorescent protein, or enhanced yellow fluorescent protein [eYFP]) that mark cells that have activated the IL-17F 84,89,90 or IL-17A 91 programme. There are some general conclusions regarding Th17 stability that can be drawn from these studies.…”
Section: Th17 Cells a Heterogeneous And Plastic Populationmentioning
confidence: 99%
“…These experiments have revealed that in-vitrogenerated Th17 cells lose their IL-17 expression and start to secrete IFN-c following transfer to T-cell-deficient mice. [83][84][85]89 One of these studies employed the T-cell transfer model and Th17 cells (purified based on Thy1.1 expression marking activation of the IL-17F programme) and showed that some of these cells when recovered from mesenteric lymph nodes of colitic Rag )/) recipients had extinguished IL-17 expression and switched on IFN-c production. 84 In contrast to the Th17 phenotype switch observed in T-cell-deficient recipients, Nurieva et al 89 have reported that Th17 cells maintain their phenotype when given to T-cell-sufficient wild-type mice.…”
Section: Th17 Cells a Heterogeneous And Plastic Populationmentioning
confidence: 99%